IMAGING OF VITELLIFORM MACULAR LESIONS USING POLARIZATION-SENSITIVE OPTICAL COHERENCE TOMOGRAPHY. Issue 3 (March 2019) - Deák, Gábor G.; Schmidt, Wolfgang M.; Bittner, Reginald E.; Mylonas, Georgios; Roberts, Philipp K.; Zotter, Stefan; Baumann, Bernhard; Pircher, Michael; Hitzenberger, Christoph K.; Schmidt-Erfurth, Ursula M.; Ritter, Markus
Abstract : Purpose: To examine the involvement of the retinal pigment epithelium (RPE) in the presence of vitelliform macular lesions (VML) in Best vitelliform macular dystrophy (BVMD), autosomal recessive bestrophinopathy, and adult-onset vitelliform macular degeneration using polarization-sensitive optical coherence tomography (PS-OCT). Methods: A total of 35 eyes of 18 patients were imaged using a PS-OCT system and blue light fundus autofluorescence imaging. Pathogenic mutations in the BEST1 gene, 3 of which were new, were detected in all patients with BVMD and autosomal recessive bestrophinopathy. Results: Polarization-sensitive optical coherence tomography showed a characteristic pattern in all three diseases with nondepolarizing material in the subretinal space consistent with the yellowish VML seen on funduscopy with a visible RPE line below it. A focal RPE thickening was seen in 26 eyes under or at the edge of the VML. Retinal pigment epithelium thickness outside the VML was normal or mildly thinned in patients with BVMD and adult-onset vitelliform macular degeneration but was diffusely thinned or atrophic in patients with autosomal recessive bestrophinopathy. Patients with autosomal recessive bestrophinopathy showed sub-RPE fibrosis alongside the subretinal VML. Polarization-sensitive optical coherence tomography was more reliable in assessing the localization and the integrity of the RPE than spectral domain OCT alone. On spectral domain OCT, identification of the RPE was not possible in 19.4% of eyes. Polarization-sensitive optical coherence tomography allowed for definite identification of the location of VML in respect to the RPE in all eyes, since it provides a tissue-specific contrast. Conclusion: Polarization-sensitive optical coherence tomography confirms in vivo the subretinal location of VML and is useful in the assessment of RPE integrity. Abstract : Polarization-sensitive optical coherence tomography is useful for assessing the condition and localization of the retinal pigment epithelium in vitelliform macular lesions.